Impacts of doping concentration on the saturable characteristics of Tm-Ho codoped fiber saturable absorber. (1st March 2018) - Tao, Mengmeng; Feng, Guobin; Yu, Ting; Ye, Xisheng; Wang, Zhenbao; Shen, Yanlong; Zhao, Jun
Highlights: Temporal evolution and energy transition processes are examined and compared. Impacts of dopant concentrations are analyzed and discussed. The concentration ratio can be optimized for desired applications. Abstract: Impacts of Tm ion concentration and Ho ion concentration on the saturable behaviors of Tm-Ho codoped fiber saturable absorbers and the output characteristics of the passively Q-switched laser systems are investigated and analyzed both at the initial lasing state and the stable passive Q-switching state. Simulations show that, varying concentrations of Tm and Ho ions have different impacts on the temporal evolution processes but similar effects on the macroscopic characteristics of the laser system. The root for the impacts of dopant concentrations is the population of the 3 H6 energy level and the cavity loss it induces. For Tm ions, the rise of the Tm concentration improves the population of the 3 H6 energy level directly, while, for Ho ions, higher Ho concentration leads to larger recovery rate of the 3 H6 energy level, thus increasing the population of the 3 H6 energy level indirectly. As for limited total dopant concentration, the Tm:Ho concentration ratio can be optimized for different applications.